Analisis manajemen corporate social responsibility di Rumah Sakit Nur Hidayah Bantul - Muhammad Cahyo Wicaksono; Ahmad Ahid Mudayana (Berita Kedokteran Masyarakat (BKM), 2018)
Analysis of management corporate social responsibility (CSR) at Nur Hidayah Hospital In BantulPurpose: Analyzing the management of Corporate Social Responsibility (CSR) at Nur Hidayah Hospital in Bantul.Methods: This was qualitative research using a descriptive case study design. The key informants were Director of Hospital, PKRS Coordinator and 2 PKRS Staff using techniques purposive sampling. Methods of data collection using in-depth interviews and observations. The validity of the data uses source triangulation.Results: Based on Management Functions: 1) the planning CSR program was well planned. 2) organizing CSR program has been already well run completed with the Duties and Powers (UTW). 3) in implementation there was an obstacles, the lack of human resources, miscommunication and limitations partners 4) monitoring of CSR program carried out from internal side of the hospital and external / partners. 5) evaluation of CSR program has been already running on a regular basis and in accordance with the used quality standards.Conclusions: The management function in the CSR Program at Nur Hidayah Hospital in Bantul when viewed as a whole has not been said to be perfect but has been running with all it should even though there are still some obstacles that can be overcome by employees and PKRS Team